An exploratory study of the online engagement with the Generation Y and its management on Facebook by the luxury wine brands of the Rhône Valley. - LAMBERT, Claire (2015)
The luxury industry has changed with regard to luxury wine brands. Before they were focused on employing the traditional marketing communications in order to build their brand image with some adjectives such as "tradition", "savoir-faire" and “terroir”, but now with the power of social media and their users, it is time to change the rules and innovate in order to engage with the new consumers: the generation Y consumers that were born with the use of the Internet at their fingertips. The use of social media and especially by luxury wine brands is a very contradictory topic because of the conflict between the accessibility of social media, indeed everyone is free to post and comment on every subject, and the exclusive appeal of wine luxury brands. This exploratory study corrects the gaps in the literature with regard to social media marketing and luxury wine brands. Moreover, much research has been done in the Australian and American vineyards but none has been focused on the Rhône Valley that is the second biggest French wine region. This study adopts a qualitative methodology using semi-structured interviews of different wine managers in order to offer new insights about the management of social media especially on Facebook in order to engage with the generation Y. The findings confirm that the engagement with this generation is still difficult to create for luxury wine brands because of the novelty and the lack of knowledge about social media management. The findings also identified the different impact that Facebook can have on the brand image. To finish, some theoretical and practical implications for managers about enhancing the visibility of luxury wines are discussed.